Transforming Outreach Effects: The Impact of Generative AI on Inclusive Education Branding and Sustainability - Guspian, Iza; Lin , Chien-Chang; YuQing Huang , Anna; J. H. Yang, Stephen (Journal of Education For Sustainable Innovation, 2024)
Generative AI's effect on inclusive education is a revolutionary potential in strengthening the branding strategies of educational institutions dedicated to inclusive education is examined in branding and sustainability. It answers important research questions on how generative AI is now being used in branding, the technological settings it provides for students from marginalized backgrounds, and the benefits and problems that come with it. According to result, generative AI can enhance accessibility through adaptive technologies, personalize outreach through tailored messages, and boost engagement through immersive and gamified learning environments. It also encourages the production of varied content and gripping narratives that showcase the accomplishments of underrepresented students. Challenges and opportunities are also revealed by the study, such as the need for appropriate data management to preserve student trust and ethical concerns over bias in AI models. Implementation efforts are made more difficult by technical constraints like guaranteeing the caliber and accessibility of AI-generated material. All things considered, this study highlights how generative AI might promote sustainability and inclusion in education while highlighting the necessity of resolving these issues to optimize its effects.